Economic Feasibility Analysis and Marketing Strategy of Broiler Chicken Farming at “AA Farm” Company in Tanggulun Village, Kadungora District, Garut Regency - Nugraha, Nugraha; Putra, Yuda Dharma; Hurriyati, Ratih (Dinasti Publisher, 2026)
Broiler farming is a strategically important sector within Indonesia’s national food industry, driven by steadily rising per capita chicken meat consumption. This study aims to (1) evaluate the economic feasibility of the broiler farming enterprise “AA Farm” in Tanggulun Village, Kadungora District, Garut Regency, and (2) formulate a comprehensive marketing strategy to support its sustainable growth. A single-case-study design with a quantitative descriptive approach was employed. Primary data were gathered through in-depth interviews, direct field observations, and structured questionnaires, while secondary data were drawn from company financial records, market reports, and official government publications. Economic feasibility was assessed using Total Cost (TC), Total Revenue (TR), profit (π), Revenue–Cost (R/C) Ratio, and Break-Even Point (BEP) analyses. The findings reveal that “AA Farm” achieves its Break-Even Point at the 17th production cycle (≈17 months), with an annual Return on Investment (ROI) of 47% and an R/C Ratio of 1.40, confirming strong operational profitability. The marketing strategy, built on the Marketing Mix (4P) framework and SWOT analysis, encompasses targeted market segmentation across four consumer groups, cost-plus competitive pricing, a multi-channel distribution system, integrated digital and traditional promotion, and a customer relationship management (CRM) programme. These findings demonstrate that “AA Farm” is economically feasible and possesses substantial potential for sustainable growth when supported by disciplined marketing implementation and modern operational management.